Proteomic analysis of heat treated bitter gourd (Momordica charantia L. var. Hong Kong Green) using 2D-DIGE - Ng, Z.X.; Chua, K.H.; Kuppusamy, U.R. (Elsevier, 2013)
This study aimed to investigate the changes in the proteome of bitter gourd prior to and after subjecting to boiling and microwaving. A comparative analysis of the proteome profiles of raw and thermally treated bitter gourds was performed using 2D-DIGE. The protein content and number of protein spots in raw sample was higher when compared to the cooked samples. Qualitative analysis revealed that 103 (boiled sample) and 110 (microwaved sample) protein spots were up regulated whereas 120 (boiled sample) and 107 (microwaved sample) protein spots were down regulated. Ten protein spots with the highest significant fold change in the cooked samples were involved in carbohydrate/energy metabolisms and stress responses. Small heat shock proteins, superoxide dismutase, quinone oxidoreductase, UDP-glucose pyrophosphorylase and phosphoglycerate kinase play a role in heat-stress-mediated protection of bitter gourd. This study suggests that appropriate heat treatment (cooking methods) can lead to induction of selected proteins in bitter gourd.